Fundus flavimaculatus: Clinical images and review of literature - Kumar, Rajiv; Singh, Shilpa; Narula, Anurag; Kumar, Manish (Indian Journal of Case Reports, 2018)
Stargardt disease (STGD) or fundus flavimaculatus is a progressive form of juvenile macular degeneration with considerableclinical and genetic heterogeneity. It may be considered a syndromal cone-rod dystrophy due to overlapping clinical features suchas loss of color vision and photophobia in some patients. Here, we report a case of fundus flavimaculatus in a 32-year-old femaleand discuss the literature pertaining to it. Clinical data including medical history, findings on physical examination and localexamination were suggestive of fundus flavimaculatus. Best-corrected visual acuity of the patient remained constant at 6/12 for1 year with the patient being on 3-month follow-up. No particular or specific treatment is available for this fundus dystrophy andfrequent follow-ups may help diagnose and manage associated choroidal neovascular membrane at the earliest. The only modalityis available in the form of low vision aids for advanced disease.